2013
DOI: 10.1371/journal.pone.0076388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcatheter Intraarterial Therapies on the Distribution of Doxorubicin in Liver Cancer in a Rabbit Model

Abstract: Background and AimsTranscatheter intraarterial techniques can effectively deliver chemotherapeutic agents to tumor and improve the efficacy of chemotherapy. The present study is designed to evaluate the effect of transcatheter intraarterial techniques on the distribution of doxorubicin in relation to blood vessels in liver cancer.MethodsVX2 tumors were implanted in the livers of 32 rabbits. The animals were divided into 4 groups of 8 animals each. Group 1 (doxo iv) animals received doxorubicin intravenous inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Together with those results, the results of this second part of the study clearly showed that lipiodol alone does not interact directly with DOX membrane transport, and indicate that it is the properties of the complete lipiodol‐based parenteral formulation of DOX that result in its increased tumour‐directed delivery . In fact, it has been demonstrated in other studies that the properties of the formulation may be important for the delivery of DOX to the tumour in vivo . Lipid transport in the body is dependent on lipoproteins, fatty acid binding proteins, lipid transporters (such as ABC transporters), endocytosis and lymphatic drainage .…”
Section: Discussionsupporting
confidence: 59%
“…Together with those results, the results of this second part of the study clearly showed that lipiodol alone does not interact directly with DOX membrane transport, and indicate that it is the properties of the complete lipiodol‐based parenteral formulation of DOX that result in its increased tumour‐directed delivery . In fact, it has been demonstrated in other studies that the properties of the formulation may be important for the delivery of DOX to the tumour in vivo . Lipid transport in the body is dependent on lipoproteins, fatty acid binding proteins, lipid transporters (such as ABC transporters), endocytosis and lymphatic drainage .…”
Section: Discussionsupporting
confidence: 59%
“…When given systemically, doxorubicin has a poor penetration through cancer tissue due to its avid binding to DNA and sequestration in endosomes by perivascular cells (51, 52). However, intraarterial administration of doxorubicin with TACE demonstrated improved drug penetration into tumor tissue compared to systemic therapy (53). Evofosfamide showed the ability to enhance the activity of commonly used systemic chemotherapeutics agents, notably doxorubicin, in xenograft models (14, 44).…”
Section: Discussionmentioning
confidence: 99%
“…DOX was mostly distributed only around the tumor blood vessels 4 h after intra-arterial administration [82]. Drug penetration was enhanced with LIP, but adjacent avascular regions were never reached with DOX [82].…”
Section: In Vivo Behavior Of Lipdox In the Hepatobiliary Systemmentioning
confidence: 99%
“…Even though co-administration of DOX with LIP (unknown composition) increased tumor DOX concentrations, the intra-tumor distribution of the iodine component of LIP did not predict the intratumor distribution of DOX [80,81]. DOX was mostly distributed only around the tumor blood vessels 4 h after intra-arterial administration [82]. Drug penetration was enhanced with LIP, but adjacent avascular regions were never reached with DOX [82].…”
Section: In Vivo Behavior Of Lipdox In the Hepatobiliary Systemmentioning
confidence: 99%
See 1 more Smart Citation